BBR 3464: a novel triplatinum complex, exhibiting a preclinical profile of antitumor efficacy different from cisplatin - Manzotti, C; Pratesi, G; Menta, E; Di Domenico, R; Cavalletti, E; Fiebig, H H; Kelland, L R; Farrell, N; Polizzi, D; Supino, R; Pezzoni, G; Zunino, F (Clinical cancer research, 2000)
Multinuclear platinum complexes represent a new class of anticancer agents, distinct in terms of DNA binding features and the profile of antitumor activity from their mononuclear counterparts, in particular cisplatin. Among complexes of this class, BBR 3464, a trinuclear platinum compound has been selected for preclinical development. In the present study, we describe the preclinical evaluation of BBR 3464 in a series of human tumor cell lines and tumor xenografts, with special emphasis on tumor types known to be resistant to cisplatin. In a panel of seven human tumor cell lines naturally resistant to cisplatin (three ovarian and four melanomas), BBR 3464 was extremely potent with IC50 values at least 20-fold lower than cisplatin. Against eight human tumor xenografts including four tumors refractory to cisplatin, BBR 3464 was confirmed to be very active with a tumor weight inhibition >80% in seven of them. The efficacy of BBR 3464 against cisplatin-resistant tumors was consistent with the ability of the drug to completely overcome resistance in three cell systems characterized by acquired resistance to cisplatin. Moreover, BBR 3464 caused a more prolonged effect than cisplatin, which was reflected by higher specific growth delay values. This prolonged effect is likely to be related to a more persistent perturbation of the cell cycle induced by BBR 3464 than by cisplatin, as shown in one ovarian tumor cell line. Finally, the profile of sensitivity to BBR 3464 within the 60-cell-lines screening panel of the National Cancer Institute, NIH (Bethesda, MD) differed from those of established drugs, thus supporting the hypothesis of a distinct mechanism of cytotoxic activity of BBR 3464. The novel trinuclear platinum complex, in light of its innovative antitumor activity profile, has the potential to become a useful clinical agent for the treatment of unresponsive tumors.